Anne Tyler - Evans, Elizabeth, 1935- (New York : Twayne Publishers, 1993)
Comprehensive evaluation introducing readers to Tyler the short story writer and critic as well as novelist.
Includes bibliographical references (p. 163-169) and index.
Choice.
Reference and Research Book News.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Tyler, Anne -- Criticism and interpretation; Tyler, Anne -- Criticism; Women and literature -- United States -- History -- 20th century; Baltimore (Md.) in literature; Women and literature -- History; Baltimore (Md.) -- In literature